Faktor Faktor Yang Mempengaruhi Nilai Perusahaan Pada Perusahaan Manufaktur - Erlina Cintya Dewi, Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of this study was to determine the relationship between profitability, capital structure, dividend policy, liquidity and firm size on firm value in manufacturing companies listed on the IDX. The sample used is a manufacturing company listed on the Indonesia Stock Exchange in the period 2015-2017. This study used a sample of 35 companies and used SPSS version 23. Sampling was done using purposive sampling method. The results in this study indicate that profitability, capital structure, and firm size have a significant influence on firm value, while dividend policy and liquidity do not have a significant effect on firm value